2009
DOI: 10.1213/ane.0b013e3181b65ea0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Gabapentin and Ketamine in Acute and Chronic Pain After Hysterectomy

Abstract: Gabapentin and ketamine are similar in improving early pain control and in decreasing opioid consumption; however, gabapentin also prevented chronic pain in the first 6 postoperative months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 25 publications
4
107
2
4
Order By: Relevance
“…In the first study, postoperative pain scores were significantly lower in patients treated with gabapentin as compared to patients who received ketamine or placebo. In this trial, a 0.3 mg/kg intravenous (IV) bolus and 0.05 mg/ kg per hour infusion of ketamine was not found to be significantly different to placebo [25]. In a study of 120 patients, Dullenkopf [55] did not find a difference in pain scores at 3 months between patients treated with placebo and either 0.15 mg/kg ketamine IV or 0.5 mg/kg ketamine IV given pre-incision.…”
Section: Ketaminementioning
confidence: 64%
See 1 more Smart Citation
“…In the first study, postoperative pain scores were significantly lower in patients treated with gabapentin as compared to patients who received ketamine or placebo. In this trial, a 0.3 mg/kg intravenous (IV) bolus and 0.05 mg/ kg per hour infusion of ketamine was not found to be significantly different to placebo [25]. In a study of 120 patients, Dullenkopf [55] did not find a difference in pain scores at 3 months between patients treated with placebo and either 0.15 mg/kg ketamine IV or 0.5 mg/kg ketamine IV given pre-incision.…”
Section: Ketaminementioning
confidence: 64%
“…However, at the 6-month time-point, it is important to recognize that only two studies were included in the analysis [23,24]. In two studies that were excluded from Sen et al [25,26], postoperative pain scores were significantly lower in the gabapentin group compared with both the ketamine and control groups at 3-and 6-month follow-up following hysterectomy and inguinal herniorrhaphy, respectively. In the remaining excluded gabapentin trial, no significant difference was found between gabapentin and placebo for pain characteristics at 6 months [27].…”
Section: Gabapentinmentioning
confidence: 99%
“…The analgesic effect of gabapentin was detected in the study of Sen et al [38] in patients undergoing abdominal hysterectomy, which compared the effect of gabapentin 1200 mg to ketamine group which ingested oral placebo capsules, then IV bolus of ketamine 0.3 mg/kg before incision then 0.05 mg/kg/hour IV infusion of ketamine until the end of operation; they detected that group received gabapentin had significantly lower pain scores compared to ketamine and control groups with significant decreased opioid requirement in gabapentin and ketamine groups compared to control group (P < 0.001).…”
Section: Discussionmentioning
confidence: 94%
“…Bulgularımıza benzer olarak, Sen ve ark., [27] histerektomi sonrası akut ve kronik ağrıda ketamin ve gabapentini karşılaştırdıkları çalışmada, ameliyat öncesi olarak bir gruba ketamin 0.3 mg/kg/ IV verilmiştir. Diğer gruba oral yolla gabapentin verilmiş.…”
Section: Discussionunclassified